2007
DOI: 10.1080/07853890701538040
|View full text |Cite
|
Sign up to set email alerts
|

Can magnetocardiography detect patients with non‐ST‐segment elevation myocardial infarction?

Abstract: Our study showed that MCG has potential clinical application for detection of NSTEMI and should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Previous studies have confirmed specific MCG findings in ischemic heart disease patients, and these investigations focused on the diagnostic value of MCG modality 91011. However, whether specific MCG findings could predict prognosis had not yet been elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have confirmed specific MCG findings in ischemic heart disease patients, and these investigations focused on the diagnostic value of MCG modality 91011. However, whether specific MCG findings could predict prognosis had not yet been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies for diagnosis of ischemic heart disease using MCG suggests several MCG parameters, such as maximum current angle, distance of poles in current density vector (CDV), field map angle in MF maps and dipole or non-dipole patterns in T-peak, have significant correlation with myocardial ischemia 91014…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, MCG is much more sensitive to very weak cardiac signals [45]. In various clinical studies superior sensitivity of MCG for ischemic myocardium at rest, as well as under stress has already been shown [14,15,30,31,50]. Recently, MCG has been recognized for its outstanding ability to detect patients with coronary artery disease [11,13,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…The possible value of resting MCG investigations has been demonstrated by various working groups 121314151617. Specifically, bundle branch block (BBB) can obscure ECG diagnosis, and its presence is associated with a 50% higher false-positive admission rate in patients with suspected ACS 1819.…”
mentioning
confidence: 99%